2006
DOI: 10.1111/j.1399-3054.2006.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relative contributions of phytochelatins and the cell wall to cadmium resistance in white lupin

Abstract: In response to Cd stress, higher plants utilise a number of defence systems, such as retention in cell walls, binding by organic molecules in the cytosol and sequestration in the vacuole. White lupin is a Cd-resistant legume that is of interest for phytoremediation of acidified and Cd-contaminated soils. The aim of this research was to evaluate the contributions of various mechanisms of Cd detoxification used by this species, focusing on cell-wall retention and binding by thiol-rich compounds. Retention of Cd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 43 publications
(55 reference statements)
1
39
1
1
Order By: Relevance
“…5a, b). In white lupin, a greater than 6 M Cd treatment disabled binding of a large part of Cd to cell walls and increased Cd inXux and caused toxicity (Vázquez et al 2006). These observations suggest that not only the Cd accumulation in cell walls, but also antioxidative abilities and vacuolar compartmentation are all important for resistance to Cd toxicity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…5a, b). In white lupin, a greater than 6 M Cd treatment disabled binding of a large part of Cd to cell walls and increased Cd inXux and caused toxicity (Vázquez et al 2006). These observations suggest that not only the Cd accumulation in cell walls, but also antioxidative abilities and vacuolar compartmentation are all important for resistance to Cd toxicity.…”
Section: Discussionmentioning
confidence: 96%
“…The Cd distribution in cell walls of T. caerulescens is indicated as one major mechanism in Cd detoxiWcation as well as vacuolar compartmentation (Cosio et al 2004(Cosio et al , 2005. The capacity of root cell walls in binding Cd 2+ is indicated as an important factor determining the Cd inXux into cells (Nishizono et al 1989;Lozano-Rodriguez et al 1997;Vázquez et al 2006). In this study, we evaluated Cd distribution to cell walls in black oat cultivars diVering in Cd sensitivity (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, other mechanisms that contribute to NO-induced increase of Cd tolerance remains unclear. The production of phytochelatins (PCs) is the secondarily eVective mechanism of Cd detoxiWcation in white lupin (Vázquez et al 2006), and the functions of PCs in Cd tolerance have been widely proved (cobbett 2000). It has been shown that Cd accumulation is accompanied by a rapid induction of PCs biosynthesis and that the content of PCs is theoretically suYcient to chelate all Cd taken up; this protects photosynthesis but does not prevent a decline in the transpiration rate (Haag-Kerwer et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Since previous evidence supports that NO aVects cellulose content in tomato roots cell walls in a dose-dependent manner (Correa-Aragunde et al 2008) and plant cell wall plays a key role in reducing Cd accumulation in the protoplast (Vázquez et al 2006), it was hypothesized that NO could be involved in the regulation of root cell wall composition in alleviating heavy Cd toxicity to plants. This study provides the Wrst evidence indicating that exogenous NO alleviates Cd toxicity to rice by increasing pectin and hemicellulose contents in root cell wall, increasing Cd accumulation in root cell wall and decreasing Cd accumulation in soluble fraction of leaves.…”
Section: Introductionmentioning
confidence: 99%